Beyond the walled city : colonial exclusion in Havana - García, Guadalupe, 1975- (Fletcher Jone Foundation Humanities Imprint, 2016)
"Once one of the most important port cities in the New World, Havana was a model for the planning and construction of other colonial cities. This book tells the story of how Havana was conceived, built, and managed and explores the relationship between colonial empire and urbanization in the Americas. Guadalupe García shows how the policing of urban life and public space by imperial authorities from the sixteenth century onward was explicitly centered on politics of racial exclusion and social control. She illustrates the importance of colonial ideologies in the production of urban space and the centrality of race and racial exclusion as an organizing ideology of urban life in Havana. Beyond the Walled City connects colonial urban practices to contemporary debates on urbanization, the policing of public spaces, and the urban dislocation of black and ethnic populations across the region"--Provided by publisher.